Harnessing the power of information technology in innovative management education - Луценко, Світлана Миколаївна (Pedagogy of Higher and Secondary Education, 2013)
Lutsenko S. N. Harnessing the power of information technology in innovative management education. In article consider the problems of implementing management to information system education. Attention is focused on the interaction between local governments, education departments and schools when applying Education Management Information System in Sumy region.